2015
DOI: 10.1590/1807-1929/agriambi.v19n3p238-244
|View full text |Cite
|
Sign up to set email alerts
|

Cinética de secagem de folhas de timbó (Serjania marginata Casar)

Abstract: R E S U M OPropôs-se, neste trabalho, avaliar a cinética de secagem de folhas de timbó (Serjania marginata Casar) e ajustar diferentes modelos matemáticos aos valores experimentais de razão de umidade. As folhas de timbó foram colhidas com teor de água inicial de 2,03 ± 0,10 decimal b.s., sendo submetidas à secagem sob condições controladas de temperatura (40, 50, 60 e 70 °C), até o teor de água de 0,08 ± 0,02 decimal b.s. Aos dados experimentais foram ajustados dez modelos matemáticos utilizados para represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
40
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 24 publications
7
40
0
9
Order By: Relevance
“…Gibbs free energy increase with the increment in temperature, as observed by Martins et al (2015). This behavior is expected, because it establishes the non-spontaneity or spontaneity of the sorption process (McMinn et al, 2005), that is, it is necessary to introduce energy from outside of the product for the process to occur.…”
Section: Resultsmentioning
confidence: 75%
“…Gibbs free energy increase with the increment in temperature, as observed by Martins et al (2015). This behavior is expected, because it establishes the non-spontaneity or spontaneity of the sorption process (McMinn et al, 2005), that is, it is necessary to introduce energy from outside of the product for the process to occur.…”
Section: Resultsmentioning
confidence: 75%
“…Effective diffusion coefficients between 0.66 x 10 -11 and 12.07 x 10 -11 m 2 s -1 were reported by Martins et al (2015) for the drying of 'timbó' leaves within the temperature range from 40 to 70 °C, respectively. Lower values were obtained for the effective diffusion coefficients of 'jambu' leaves crushed mass, which ranged between 5.79 x 10 -10 and 2.03 x 10 -9 m 2 s -1 for the thicknesses of 0.005 and 0.010 m, respectively.…”
Section: Resultsmentioning
confidence: 97%
“…The activation energy (E a ) for the drying of 'jambu' leaves crushed mass was equal to 16.61 kJ mol -1 for the thickness of 0.005 m and to 16.97 kJ mol -1 for the thickness of 0.010 m. Goneli et al (2014a), studying the drying of 'erva baleeira' leaves, reported activation energy of 62.89 kJ mol -1 . Rocha et al (2012) found E a of 77.16 kJ mol -1 in the drying of thyme, whereas Goneli et al (2014b) reported 74.96 kJ mol -1 for the drying of aroeira leaves and Martins et al (2015) obtained 81.39 kJ mol -1 in the drying of 'timbó' leaves. Lower E a values in the 'jambu' leaves crushed mass evidenced the need for lower energy to trigger the water diffusion process, in comparison to the leaves of 'erva baleeira' , thyme, aroeira and 'timbó' .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive value is characteristic of adding energy during the drying process, relating the drying of garlic to an endergonic reaction . OLIVEIRA et al (2015), CORRÊA et al (2010) andMARTINS et al (2015) showed similar values for strawberry, coffee cherry and timbó leaf drying studies, respectively. According to OLIVEIRA et al (2015), a non-spontaneous reaction is related to the enthalpy and entropy values, described above, as these reactions occur only when changes in enthalpy are positive and changes in entropy are negative; the variations of these parameters have a positive effect, but the variations are larger for the enthalpy than for the entropy; the changes in the parameters themselves are negative, and the enthalpy change is smaller than the entropy.…”
Section: Thermodynamic Parametersmentioning
confidence: 60%